2013
DOI: 10.1590/s0100-83582013000200023
|View full text |Cite
|
Sign up to set email alerts
|

Deriva simulada do glyphosate em cultivares de café Acaiá e Catucaí

Abstract: RESUMO -O objetivo desta pesquisa foi avaliar os efeitos da deriva simulada de glyphosate sobre o crescimento inicial de dois cultivares de café de crescimento distinto. Utilizou-se o delineamento em blocos casualizados com quatro repetições, sendo os tratamentos distribuídos em esquema fatorial 2x5. No primeiro fator foram alocados os cultivares e, no segundo, as subdoses do glyphosate (0, 57,6; 115,2; 230,4; e 460,8 g ha -1 ). No dia da aplicação e também aos 45 e 120 dias após aplicação (DAA), avaliaram-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
4
9
1
4
Order By: Relevance
“…Likewise, Tuffi Santos et al (2008) chose eucalyptus plants with symptoms of Glyphosate intoxication ranging from 0 to 50% of the dose in the field and verified that, after 180 days of application, the plants were recovered. No significant differences were observed in the coffee seedlings for the characteristics related to the root system, and these results differ from those found by França et al (2013), in which the authors found differences in root dry matter for cultivars Acaiá and Catuaí, using with up to 32% of the recommended herbicide dose. However , Wagner Jr. et al (2008) also reported that doses of Glyphosate applied on yellow passion fruit seedlings did not lead to reductions in root length at 28 DAA, up to 24 % of the recommended herbicide dose, corroborating the results of this study.…”
Section: Resultscontrasting
confidence: 96%
“…Likewise, Tuffi Santos et al (2008) chose eucalyptus plants with symptoms of Glyphosate intoxication ranging from 0 to 50% of the dose in the field and verified that, after 180 days of application, the plants were recovered. No significant differences were observed in the coffee seedlings for the characteristics related to the root system, and these results differ from those found by França et al (2013), in which the authors found differences in root dry matter for cultivars Acaiá and Catuaí, using with up to 32% of the recommended herbicide dose. However , Wagner Jr. et al (2008) also reported that doses of Glyphosate applied on yellow passion fruit seedlings did not lead to reductions in root length at 28 DAA, up to 24 % of the recommended herbicide dose, corroborating the results of this study.…”
Section: Resultscontrasting
confidence: 96%
“…This result evidences the negative effects caused by glyphosate intoxication in coffee plants (FRANÇA et al, 2010a;FRANÇA et al, 2010b;FRANÇA et al, 2013).…”
Section: Resultssupporting
confidence: 63%
“…Foi observado um maior efeito de estresse para a Catuaí IAC 144 e um menor efeito para a Catiguá MG2. Possivelmente, a maior interceptação de herbicida devido a uma maior área foliar de Catuaí IAC 144 provocou sintomas de estresse mais visíveis quanto ao aparato fotossintético, conforme sugerido por França et al (2013).…”
Section: Resultsunclassified
“…As cultivares Catiguá MG2 e Catuaí IAC 144 obtiveram menores valores de intoxicação, considerando que estas possuem porte médio e pequenas dimensões, respectivamente. França et al (2013), avaliando a porcentagem de intoxicação de duas cultivares de café, com crescimento distinto, constataram que plantas de café com porte maior são mais suscetíveis à deriva de glyphosate, fato que pode ser explicado pela distância maior entre os internódios, criando uma maior área de contato entre as gotas aspergidas na aplicação.…”
Section: Resultsunclassified
See 1 more Smart Citation